2003
DOI: 10.1086/377560
|View full text |Cite
|
Sign up to set email alerts
|

High Seroprevalence of Bloodborne Viruses among Street‐Recruited Injection Drug Users from Buenos Aires, Argentina

Abstract: Injection drug use is the main mechanism of human immunodeficiency virus (HIV) transmission in Argentina (40% of reported AIDS cases in Argentina). This study was conducted among street-recruited injection drug users (IDUs) from Buenos Aires, with the aim of estimating seroprevalence and coinfection of HIV, hepatitis B virus (HBV), hepatitis C virus (HCV), and human T-lymphotropic viruses (HTLVs). A total of 174 volunteers participated in this study; 137 were men (78.7% of volunteers). The average age of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
1
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 4 publications
4
37
1
2
Order By: Relevance
“…Similar HCV prevalence rates have been demonstrated among HIV-contaminated populations in France, Germany, Switzerland, and Greece [10]. Observation among urban IDU found coinfection prevalence rates of 84% and 88% [19][20][21].…”
Section: Selvaraj and Piramanayagamsupporting
confidence: 76%
“…Similar HCV prevalence rates have been demonstrated among HIV-contaminated populations in France, Germany, Switzerland, and Greece [10]. Observation among urban IDU found coinfection prevalence rates of 84% and 88% [19][20][21].…”
Section: Selvaraj and Piramanayagamsupporting
confidence: 76%
“…The non-injecting-drug population may be at greater risk of sexual transmission of HCV as a result of increased exposure to possibly HCV-infected IDU 3,19,20 . We should also not rule out that some NICU have a history of IDU that was not reported during the interview, or another form of blood exposure with their IDU partner, such as sharing razor blades or toothbrushes.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies on the prevalence of infections that are either bloodborne or sexually acquired among drug users in Argentina have been conducted among injecting drug users (IDU), over 95% of whom inject cocaine. Several studies have demonstrated a high seroprevalence of human immunodeficiency virus (HIV), hepatitis B virus (HBV), and hepatitis C virus (HCV) 2,3,4,5 among the drug-injecting population. Cocaine, which was regarded several decades ago as a drug consumed exclusively by affluent people, has now extended into low-income sectors that were formerly far from its reach.…”
Section: Introductionmentioning
confidence: 99%
“…The results yielded an HIV seroprevalence of 44.3%. Only 6.5% of the HIV-infected IDUs were not co-infected with other viruses; 88.3% of them were coinfected with hepatitis C virus (HCV) and 68.6% with hepatitis B virus (HBV) (49). A survey carried out in four different regions of Argentina (Córdoba, Rosario, Mar del Plata, and Buenos Aires) corroborated these findings, and reinforced the disquieting picture of high levels of sharing of injection equipment and high rates of HIV infection among IDUs from all four sites (50).…”
Section: The Southernmentioning
confidence: 99%